COVID-19 and visual arts education: Bibliographic review for a post-pandemic citizenship - Pillacela-Chin, Luisa Alejandrina (Street Art & Urban Creativity, 2025)
The purpose of this article is to analyze the research on university education in the visual arts in the context of COVID-19, in order to find out which were the most relevant concepts on the subject. The methodology was the systematic review of the existing literature in the databases Dialnet, ERIC, Scopus, Proquest and Google Scholar, between 2020 and 2024, based on these descriptors: visual arts; COVID/pandemic; university/higher education. A total of 36 texts were obtained. The emerging categories highlighted were: emotional affections of students and teachers, pros and cons of emergency remote teaching of visual arts, the idea that the technical instruction of artistic disciplines is not very transferable to online education, training strategies in particular cases of practical and theoretical subjects, experiences in research projects and service-learning, and the possibilities of virtuality for international teaching cooperation.